Duodenal Pyloric Gland Adenoma in a 59-Year-Old Asian Male - Mia Manabat; Matthew Jackson; Kha Ngo; Laurence Stawick (Case Reports in Gastrointestinal Medicine)
Pyloric gland adenomas (PGAs) are rare precancerous tumors typically arising from the stomach. Even more rarely do they arise in extragastric sites such as the duodenum and gallbladder. The identification of PGAs is important because they possess a risk of developing into invasive adenocarcinoma. This case report describes a 59-year-old male who presented to our office for a follow-up of a nonspecific duodenal lesion. Endoscopic ultrasound and pathology revealed a PGA with low grade dysplasia and some areas of focal high grade dysplasia. It is important that gastroenterologists are aware of these lesions and their risk of malignant transformation. More studies are needed to describe the long-term behavior of pyloric gland adenomas and to recommend appropriate endoscopic surveillance of these lesions.